Degradable Evaluation of Two Types of Biopolymers in Loam Soil - Hussain, Leqaa M.; Hassan, Salma M.; Bahia, M. Hassan S. (Iraqi Journal of Science, 2020)
Gel-biopolymers were prepared by different weights of two polymers (PVA, and PEG) dissolved with distilled water. Thick films of these polymers were prepared by using the casting method, with different thicknesses (t= 0.48, 0.34mm for PVA and t=0.58 mm for PEG). The objective of this research is to determine the viability of the organic polymer films of PEG and PVA on decomposition and the time required for their degradation in the soil. The purpose is to use these polymers in industry without leaving plastic residues along with the possibility of their application as fertilizers for soil. The results showed that PEG film was degraded during the first week, while PVA film was changed in weight from 0.3 to 0.23 g and thickness from 0.34to 0.21 cm. We also observed change in the shape of the sample along with ripples and holes during three month.